1979
DOI: 10.1080/00222895.1979.10735167
|View full text |Cite
|
Sign up to set email alerts
|

The Planning of Precision Movements

Abstract: Two experiments are reported in which subjects were required to make rapid aiming movements to targets of various sizes. Probe reaction time (RT) procedures were used to investigate the preparation of the response to the target. It was proposed that if the precision of movement was planned in advance, this would be reflected by the lengthening of RTs to probes presented during the latency phase of the response. The more precise the movement (to smaller targets) the longer will be the delays to the probes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Attentional demands can be measured using various indices, including behavioral, physiological, and subjective indices. In particular, a dual-task procedure is a behavioral index that has previously been used in many studies examining the amount of information available for the performance of a variety of perceptual motor tasks (Abernethy, 1988;Ells, 1973;Glencross & Gould, 1979;Kerr, 1975). Probe reaction time is a method that is very commonly used to measure attentional demands during the execution of a motor task in the dual-task procedure (Li & Wright, 2000;Salmoni, Sullivan, & Starkes, 1976).…”
Section: Introductionmentioning
confidence: 98%
“…Attentional demands can be measured using various indices, including behavioral, physiological, and subjective indices. In particular, a dual-task procedure is a behavioral index that has previously been used in many studies examining the amount of information available for the performance of a variety of perceptual motor tasks (Abernethy, 1988;Ells, 1973;Glencross & Gould, 1979;Kerr, 1975). Probe reaction time is a method that is very commonly used to measure attentional demands during the execution of a motor task in the dual-task procedure (Li & Wright, 2000;Salmoni, Sullivan, & Starkes, 1976).…”
Section: Introductionmentioning
confidence: 98%
“…A dual task procedure has been used in many previous studies in order to examine the amount of attention available for performance of a task across a range of perceptual motor tasks12,13,14 ) . Especially, the probe reaction time (PRT) is a method commonly used for attentional demand measurement during execution of motor tasks15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently there have been a number of attempts to measure attentional demand of movement using the probe reaction time (RT) procedure, in which the assumption is that the lengthening of RT reflects the attentional demand of the movement (Ells 1973, Kerr 1975, Glencross and Gould 1979, McLeod 1980. Glencross (1980) suggested that this procedure would be used to investigate some issues of motor control, for instance, at various stages of skill acquisition, in the comparison of skilled and unskilled operators, and in the direct comparison of tasks.…”
Section: Introductionmentioning
confidence: 99%